2019
DOI: 10.1039/c9cy00111e
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the CO2 deoxygenation to CO over oxygen vacancies of CeO2

Abstract: The reversibly regenerated oxygen vacancies of CeO2 can catalyze CO2 deoxygenation and the reaction is initially surface reaction limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…For example, CeO 2 -NC and CeO 2 -NR are reported to transform into CeO 2 -NO at high temperature in a reducible atomsphere. 120,153 This is because the CeO 2 (111) facet is thermodynamically more favorable, which is verified by both experimental and theoretical studies. 153,154 Metal doping is another method for improving CeO 2 -based catalysts.…”
Section: Reaction With Alkanessupporting
confidence: 59%
See 2 more Smart Citations
“…For example, CeO 2 -NC and CeO 2 -NR are reported to transform into CeO 2 -NO at high temperature in a reducible atomsphere. 120,153 This is because the CeO 2 (111) facet is thermodynamically more favorable, which is verified by both experimental and theoretical studies. 153,154 Metal doping is another method for improving CeO 2 -based catalysts.…”
Section: Reaction With Alkanessupporting
confidence: 59%
“…120,153 This is because the CeO 2 (111) facet is thermodynamically more favorable, which is verified by both experimental and theoretical studies. 153,154 Metal doping is another method for improving CeO 2 -based catalysts. For Ir/CeO 2 catalysts, La, Pr, and Zr doping resulted in several advantages, such as increasing the oxygen vacancy, enhancing metal dispersion, and inhibiting the aggregation of CeO 2 particles.…”
Section: Reaction With Alkanessupporting
confidence: 59%
See 1 more Smart Citation
“…The identification of discrete FeO and CeO 2 nanoparticles further confirmed that the sample was indeed a nanocomposite of FeO and CeO 2 (in agreement with XRD), as opposed to a ternary oxide phase. Since pure CeO 2 demonstrated negligible CO 2 hydrogenation activity under Xe lamp irradiation, it can be concluded that the function of CeO 2 in the FeCe-x catalysts was to (1) maintain a high dispersion of active FeO and Fe 0 components and (2) act as a cocatalyst to assist with the activation of CO 2 (e.g., under photothermal reaction conditions, CeO 2 will exist as CeO 2-x , thus activating CO 2 adsorption through surface V O ), as suggested by other reports [33][34][35] .…”
Section: Morphological Evolution Of the Fece-x Catalystsmentioning
confidence: 59%
“…The different densities of the polymer brushes on the ceria will lead to more or less active positions for catalysis. The CeO 2 surface is known for adsorbing CO 2 and creating different types of carbonates [47]. These carbonates are hydrogen carbonate, bidentate carbonate, monodentate carbonate, and bridged carbonate [48].…”
Section: Co2 Adsorptionmentioning
confidence: 99%